Green Product and Consumer Buying Interest to Customer Satisfaction (Study on Customers of The Icon Cafe Palopo City) - Yuniarti Hadi; M. Risal; Muhammad Aqsa (Institute of Computer Science (IOCS), 2022)
This research was conducted with the aim of testing the effect of Green Product on customer satisfaction and testing the effect of repurchase intention on customer satisfaction at The Icon Cafe Palopo. Quantitative methods by distributing questionnaires were used in collecting data. A total of 85 samples were used in this study. In processing the questionnaire data, SPSS 21 was used. The results showed that the Green Product variable and repurchase interest had a joint effect on customer satisfaction at The Icon Cafe Palopo. The Green Product variable partially has a positive and significant effect on customer satisfaction, and repurchase interest also has a positive and significant effect on customer satisfaction at The Icon Cafe Palopo.